Prognostic Impact of Adverse Pathologic Features in Sinonasal Squamous Cell Carcinoma - Parikh, Anuraag S.; Fuller, Jennifer C.; Lehmann, Ashton E.; Goyal, Neerav; Gray, Stacey T.; Lin, Derrick T. (Journal of Neurological Surgery Part B: Skull Base, 2020)
Objective This study aimed to describe the impact of adverse clinical and pathologic features in sinonasal squamous cell carcinoma (SCC).Design This study is designed with retrospective chart review.Setting The present study is conducted at a tertiary care institution.Participants All patients treated surgically for sinonasal SCC at our tertiary care institution between January 2006 and December 2013.Main Outcome Measures Overall survival (OS) and disease free survival (DFS) are the final measurement of this study.Results Forty-eight patients were identified. Mean age at surgery was 65.8 years, and mean follow-up time was 40.7 months. Eighteen patients (38%) had T1–T3 disease, while 30 patients (63%) had T4 disease. Seven patients (8.3%) had nodal disease at presentation. At 2, 5, and 10 years, OS was 71, 54, and 48%, respectively, while DFS was 64, 51, and 45%, respectively. Twelve patients (25%) experienced local recurrences with mean time to recurrence of 15.3 months. Twenty-five patients (52%) had positive margins, 24 (50%) had high-grade tumors, 18 (38%) had perineural invasion (PNI), and 15 (31%) had lymphovascular invasion (LVI). In the univariate analysis, T4 disease (risk ratio [RR] = 2.7) and high grade (RR = 2.4) had a significant association with DFS. In the multivariate analysis, high grade (RR = 4.0 and 4.5) and LVI (RR = 4.1 and 4.7) had a significant association with OS and DFS.Conclusion Our single-institution experience of 48 patients suggests that high grade and LVI are independently associated with survival outcomes in sinonasal SCC, while PNI and microscopically positive margins do not have a significant impact.
Keywords: sinonasal squamous cell carcinoma; lymphovascular invasion; grade; perineural invasion